2021
DOI: 10.1136/bmjopen-2020-042908
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and dental caries among Chinese preschool children: a cross-sectional national study

Abstract: ObjectivesSocioeconomic inequalities in oral health are often neglected in oral health promotion. This cross-sectional study assessed the association between dental caries and socioeconomic status (SES) among preschool children in China.DesignCross-sectional study.SettingData from the Fourth National Oral Health Survey of China (2015), comprising of 40 360 children aged 3–5 years was used.MethodsDental caries indicators including prevalence of dental caries, dental pain experience and number of decayed, missin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(43 reference statements)
2
9
0
1
Order By: Relevance
“…However, at present, father is also a care giver for the children in Sri Lankan socio-cultural context as most of the other countries and it is worthwhile to investigate educational level of both father and the mother. It was found, a significant difference of the prevalence of untreated dental caries by different levels of father's education(p=0.027).It is in agreement with the study findings exist in literature demonstrating higher prevalence of untreated dental caries among children having parents with lower education compare to children who are having parents with higher education (Zhang et al, 2021). However, the prevalence of untreated dental caries was higher among children whose fathers received education G.C.E.…”
Section: Resultssupporting
confidence: 89%
“…However, at present, father is also a care giver for the children in Sri Lankan socio-cultural context as most of the other countries and it is worthwhile to investigate educational level of both father and the mother. It was found, a significant difference of the prevalence of untreated dental caries by different levels of father's education(p=0.027).It is in agreement with the study findings exist in literature demonstrating higher prevalence of untreated dental caries among children having parents with lower education compare to children who are having parents with higher education (Zhang et al, 2021). However, the prevalence of untreated dental caries was higher among children whose fathers received education G.C.E.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, these results suggest the impact of a parents' educational level in oral health of their children and confirm the results of a previous Libyan studies [11,12]. Furthermore, similar trends were confirmed by other studies [4,10,13,15,[38][39][40][41]. Parents play a key role in their children's dental health.…”
Section: Discussionsupporting
confidence: 91%
“…Socioeconomic status relating to family income and parental education level is a widely documented risk indicator for ECC ( 4 , 21 , 22 ). In this study, the chi-square test and logistic regression analysis showed that lower family income was significantly associated with higher ECC prevalence, which was also demonstrated in children from Japan ( 23 ), America ( 24 ), Australia ( 25 ), Italy ( 26 ), and Mongolia ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no association between parental education and caries prevalence existed in a sample from Mongolia ( 27 ). The inconsistency of results among various studies may be due to the differences in study methodology, such as the study design, sample size, the time of data collection, and the methods for assessing ECC ( 21 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation